Agomelatine Improves Sleep in a Patient with Fatal Familial Insomnia - Froböse, T.; Slawik, H.; Schreiner, R.; Veselý, Z.; Wiegand, M.; Bäuml, J.; Förstl, H. (Pharmacopsychiatry, 2012)
A young patient with FFI was started on agomelatine 25 mg to medicate nocturnal insomnia. Under this treatment sleep efficiency was improved, slow wave sleep was high and awakenings during sleep period time were far less than before. Clinically the patient was less restless during nighttime.
Keywords: dementia; insomnia; melatonin